Inoculation Effect of Nitrogen-fixing and Phosphate-Solubilising Bacteria on Seed Germination of Brinjal (Solanum melongena L.) - Sharma, Tarun; Kumar, Navin; Rai, Nishant (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*309.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967272);" role="presentation">Twenty <span dir="ltr" style="left: calc(var(–scale-factor)*105.98px); top: calc(var(–scale-factor)*309.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916362);" role="presentation">rhizobacteria <span dir="ltr" style="left: calc(var(–scale-factor)*162.02px); top: calc(var(–scale-factor)*309.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952091);" role="presentation">were isolated from rhizospheric soils of Uttarakhand Tarai region. <span dir="ltr" style="left: calc(var(–scale-factor)*438.55px); top: calc(var(–scale-factor)*309.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.984094);" role="presentation">Out of 20 <span dir="ltr" style="left: calc(var(–scale-factor)*482.62px); top: calc(var(–scale-factor)*309.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910724);" role="presentation">isolates, 3 <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90047);" role="presentation">isolates (P<span dir="ltr" style="left: calc(var(–scale-factor)*114.02px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960593);" role="presentation">B2<span dir="ltr" style="left: calc(var(–scale-factor)*125.78px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906867);" role="presentation">, P<span dir="ltr" style="left: calc(var(–scale-factor)*136.82px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943727);" role="presentation">B12<span dir="ltr" style="left: calc(var(–scale-factor)*153.62px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900407);" role="presentation">, and PB<span dir="ltr" style="left: calc(var(–scale-factor)*188.93px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917882);" role="presentation">19) were <span dir="ltr" style="left: calc(var(–scale-factor)*227.69px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932351);" role="presentation">selected on the basis of morphological, biochemical, physiologically and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*335.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942748);" role="presentation">different PGP traits. The isolates were Gram negative, ca<span dir="ltr" style="left: calc(var(–scale-factor)*309.65px); top: calc(var(–scale-factor)*335.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930788);" role="presentation">talase positive, oxidase positive, starch and gelatine <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937518);" role="presentation">hydrolysis <span dir="ltr" style="left: calc(var(–scale-factor)*120.21px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933852);" role="presentation">positive. <span dir="ltr" style="left: calc(var(–scale-factor)*161.18px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*183.36px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911082);" role="presentation">bacterial <span dir="ltr" style="left: calc(var(–scale-factor)*224.38px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901483);" role="presentation">cultures <span dir="ltr" style="left: calc(var(–scale-factor)*262.63px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893586);" role="presentation">were <span dir="ltr" style="left: calc(var(–scale-factor)*288.65px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933474);" role="presentation">positive <span dir="ltr" style="left: calc(var(–scale-factor)*326.89px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*345.22px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937919);" role="presentation">indole <span dir="ltr" style="left: calc(var(–scale-factor)*376.87px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893797);" role="presentation">acetic <span dir="ltr" style="left: calc(var(–scale-factor)*406.85px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909865);" role="presentation">acid <span dir="ltr" style="left: calc(var(–scale-factor)*430.00px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928307);" role="presentation">production, <span dir="ltr" style="left: calc(var(–scale-factor)*482.49px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.867995);" role="presentation">phosphate <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945477);" role="presentation">solubilisation, ammonia production, siderophore production, and nitrogen fixing activity. <span dir="ltr" style="left: calc(var(–scale-factor)*437.35px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906411);" role="presentation">Isolate PB<span dir="ltr" style="left: calc(var(–scale-factor)*479.38px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910416);" role="presentation">19 was the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.853993);" role="presentation">be<span dir="ltr" style="left: calc(var(–scale-factor)*81.50px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.852764);" role="presentation">st <span dir="ltr" style="left: calc(var(–scale-factor)*95.42px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.1046);" role="presentation">IAA <span dir="ltr" style="left: calc(var(–scale-factor)*120.36px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90405);" role="presentation">producer <span dir="ltr" style="left: calc(var(–scale-factor)*163.25px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908094);" role="presentation">strain (<span dir="ltr" style="left: calc(var(–scale-factor)*196.13px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901314);" role="presentation">42.50<span dir="ltr" style="left: calc(var(–scale-factor)*218.69px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969032);" role="presentation">μgml-1) <span dir="ltr" style="left: calc(var(–scale-factor)*255.99px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972296);" role="presentation">while <span dir="ltr" style="left: calc(var(–scale-factor)*285.37px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90363);" role="presentation">isolate P<span dir="ltr" style="left: calc(var(–scale-factor)*324.55px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950741);" role="presentation">B2 <span dir="ltr" style="left: calc(var(–scale-factor)*343.51px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.868899);" role="presentation">was <span dir="ltr" style="left: calc(var(–scale-factor)*366.18px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922261);" role="presentation">lowest <span dir="ltr" style="left: calc(var(–scale-factor)*399.52px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.1046);" role="presentation">IAA <span dir="ltr" style="left: calc(var(–scale-factor)*424.45px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90709);" role="presentation">producer <span dir="ltr" style="left: calc(var(–scale-factor)*467.46px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927525);" role="presentation">(25<span dir="ltr" style="left: calc(var(–scale-factor)*480.94px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903951);" role="presentation">.34<span dir="ltr" style="left: calc(var(–scale-factor)*493.54px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964004);" role="presentation">μgml-1) <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.980282);" role="presentation">comparatively. All <span dir="ltr" style="left: calc(var(–scale-factor)*151.34px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*167.06px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911945);" role="presentation">three isolate<span dir="ltr" style="left: calc(var(–scale-factor)*216.65px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921682);" role="presentation">s showed siderophore production <span dir="ltr" style="left: calc(var(–scale-factor)*355.51px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*373.39px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996942);" role="presentation">nitrogen fixing activity in G-<span dir="ltr" style="left: calc(var(–scale-factor)*492.70px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02301);" role="presentation">NFMM <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*401.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9872);" role="presentation">media. Effect of <span dir="ltr" style="left: calc(var(–scale-factor)*144.50px); top: calc(var(–scale-factor)*401.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977074);" role="presentation">nitrogen fixing and phos<span dir="ltr" style="left: calc(var(–scale-factor)*247.97px); top: calc(var(–scale-factor)*401.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949987);" role="presentation">phate solubilising <span dir="ltr" style="left: calc(var(–scale-factor)*324.91px); top: calc(var(–scale-factor)*401.83px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963187);" role="presentation">PGPR alone and in different combinations was <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955426);" role="presentation">studied on seed germination of <span dir="ltr" style="left: calc(var(–scale-factor)*206.57px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.98288);" role="presentation">brinjal <span dir="ltr" style="left: calc(var(–scale-factor)*236.93px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937071);" role="presentation">plant. Treatments <span dir="ltr" style="left: calc(var(–scale-factor)*312.89px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.998812);" role="presentation">with <span dir="ltr" style="left: calc(var(–scale-factor)*334.87px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95735);" role="presentation">different <span dir="ltr" style="left: calc(var(–scale-factor)*373.51px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929798);" role="presentation">combination <span dir="ltr" style="left: calc(var(–scale-factor)*427.75px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01877);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*440.50px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924848);" role="presentation">bacterial isolates <span dir="ltr" style="left: calc(var(–scale-factor)*513.46px); top: calc(var(–scale-factor)*415.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903412);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.98288);" role="presentation">brinjal <span dir="ltr" style="left: calc(var(–scale-factor)*102.62px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.819394);" role="presentation">seeds <span dir="ltr" style="left: calc(var(–scale-factor)*128.66px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941776);" role="presentation">showed maximum <span dir="ltr" style="left: calc(var(–scale-factor)*208.73px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.997246);" role="presentation">germination %, with consortia D (T8) and treatment 4 (<span dir="ltr" style="left: calc(var(–scale-factor)*448.18px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925114);" role="presentation">PB19) <span dir="ltr" style="left: calc(var(–scale-factor)*478.30px); top: calc(var(–scale-factor)*428.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959824);" role="presentation">by 95.83% <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*441.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931388);" role="presentation">compared to control and other PGPR combinations <span dir="ltr" style="left: calc(var(–scale-factor)*285.65px); top: calc(var(–scale-factor)*441.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964943);" role="presentation">after 8 d<span dir="ltr" style="left: calc(var(–scale-factor)*321.07px); top: calc(var(–scale-factor)*441.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.85399);" role="presentation">ays <span dir="ltr" style="left: calc(var(–scale-factor)*337.75px); top: calc(var(–scale-factor)*441.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952133);" role="presentation">of incubation. <span dir="ltr" style="left: calc(var(–scale-factor)*397.75px); top: calc(var(–scale-factor)*441.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918247);" role="presentation">The consor<span dir="ltr" style="left: calc(var(–scale-factor)*443.62px); top: calc(var(–scale-factor)*441.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94465);" role="presentation">tia of three isolated <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892859);" role="presentation">bacteria <span dir="ltr" style="left: calc(var(–scale-factor)*107.54px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.855841);" role="presentation">sho<span dir="ltr" style="left: calc(var(–scale-factor)*121.46px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960864);" role="presentation">wed significant effects on <span dir="ltr" style="left: calc(var(–scale-factor)*232.25px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962827);" role="presentation">Seedling Vigour Index <span dir="ltr" style="left: calc(var(–scale-factor)*329.83px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00171);" role="presentation">(SVI), <span dir="ltr" style="left: calc(var(–scale-factor)*358.99px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929472);" role="presentation">germination index, and other associated <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908527);" role="presentation">germination parameters. <span dir="ltr" style="left: calc(var(–scale-factor)*173.78px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908435);" role="presentation">Thus, <span dir="ltr" style="left: calc(var(–scale-factor)*200.09px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944824);" role="presentation">it was concluded that <span dir="ltr" style="left: calc(var(–scale-factor)*291.65px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943597);" role="presentation">the use of combination of PGPR isolates <span dir="ltr" style="left: calc(var(–scale-factor)*464.26px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950545);" role="presentation">could improve <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881519);" role="presentation">seed germination and as<span dir="ltr" style="left: calc(var(–scale-factor)*168.26px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906065);" role="presentation">sociated parameters of brinjal.